Pengaruh Pemberian Mulsa dan Pupuk Bokashi Kotoran Kambing Terhadap Pertumbuhan dan Hasil Tanaman Bawang Daun (Allium fistulosum L) - Risman Munazar; Rian Christian Sondakh; Hayatudin Hayatudin (Permaculture: Jurnal Ilmu Pertanian & Lingkungan, 2026)
This study aims to analyze: (1) the interaction between goat manure bokashi and mulch on the growth and yield of spring onions, (2) the effect of goat manure bokashi on the growth and yield of spring onions, and (3) the effect of the use of organic and inorganic mulch on the growth and yield of spring onions. The study was conducted in May–August 2025 at the Experimental Garden of the Faculty of Agriculture, Madako University, Tolitoli. The study used a Randomized Block Design (RAK) with two factors. The first factor is the dose of goat manure bokashi (B) which consists of three treatments, namely B0 (without bokashi), B1 (20 tons/ha equivalent to 400 g/plant), and B2 (30 tons/ha equivalent to 600 g/plant). The second factor is mulch (M) which includes M0 (without mulch), M1 (organic mulch in the form of sawdust), and M2 (inorganic mulch in the form of black and silver plastic). There are 9 treatment combinations with 3 replications, resulting in 27 experimental units. Each plot contained 28 plants, with 5 plants as samples, resulting in a total of 756 main plants and 135 sample plants. The results showed that goat manure bokashi significantly affected plant height, number of leaves, number of tillers, and the length of the longest leaf. The highest dose (B2) generally gave the best results, except for root volume which was more optimal in treatment B1. The use of mulch affected several growth parameters, especially the number of leaves, number of tillers, root volume, and fresh weight per clump. Inorganic mulch (M2) tended to provide better results than other treatments. The interaction of bokashi and mulch significantly affected the number of tillers and root volume, with the combination of B2M2 producing the highest number of tillers and B1M2 producing the largest root volume. Overall, the application of goat manure bokashi combined with mulch, especially inorganic mulch, effectively increased the growth and productivity of spring onion plants.